2006
DOI: 10.1002/jat.1164
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin identification in moldy dwellings

Abstract: The objective of this study was to assess the level of macrocyclic trichothecenes (MCT), one of the most potent mycotoxins, on wall surfaces, floor dust and air samples from moldy dwellings. The study was based on an index group comprising 15 flooded dwellings contaminated by Stachybotrys chartarum or Chaetomium and a control group comprising nine dwellings without molds on visual inspection and mold sampling. Three samples were collected from each dwelling: a sample from the moldy wall, using a swab, a floor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 23 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…[25][26][27][28] Many have preferred to use mass spectrometry (MS)-based methods, especially tandem MS (MS/MS), because of the high analytical specificity. Vishwanath and co-authors published a method for the simultaneous determination of 186 fungal and bacterial secondary metabolites in indoor matrices using HPLC-MS/MS.…”
mentioning
confidence: 99%
“…[25][26][27][28] Many have preferred to use mass spectrometry (MS)-based methods, especially tandem MS (MS/MS), because of the high analytical specificity. Vishwanath and co-authors published a method for the simultaneous determination of 186 fungal and bacterial secondary metabolites in indoor matrices using HPLC-MS/MS.…”
mentioning
confidence: 99%
“…chartarum and A. versicolor are two commonly encountered molds in buildings with moisture problems (9,12,15,28) and are prominent mycotoxin producers. Thin-layer chromatography, high-performance liquid chromatography (HPLC), and enzyme-linked immunosorbent assay are techniques that have been applied for detecting some of these mycotoxins, e.g., in ceiling materials (8,10,15), in paper materials (19,26,29), in a gypsum board liner (2), in airborne dust (4,6), and in airborne particles in a home where an infant developed pulmonary hemorrhage (35). However, many have preferred to use mass spectrometry (MS)-based methods, especially tandem MS (MSMS), because of the high analytical specificity offered.…”
mentioning
confidence: 99%
“…In addition, our work has shown that these mycotoxins can be detected in the sera from persons exposed to S. chartarum within the indoor environment (Brasel et al, 2004). These results were published prior to the submission of the aforementioned manuscript (Charpin-Kadouch et al, 2006).The authors state that flooded houses were selected in their study based on the presence of S. chartarum or Chaetomium species. Both of these fungi require substrates with a water activity of >0.9 for optimal growth (Nielsen, 2003) and therefore, it would not be surprising for these organisms to be isolated together on water-saturated building materials.…”
mentioning
confidence: 90%
“…
This correspondence is in response to a paper recently published in the Journal of Applied Toxicology titled 'Mycotoxin identification in moldy dwellings' (Charpin-Kadouch et al, 2006). The authors claim their work is 'the first time direct evidence for the presence of macrocyclic trichothecenes (MCT) in moldy dwellings'.
…”
mentioning
confidence: 93%